Perhubungan antara Iklim Sekolah dan Pencapaian Prestasi Pelajar - Zalilah, Ismail (2003)
This research examined the relationship between school climate and students’ achievement in Mathematics and Science. The study involved students and teachers from three government secondary school in Kota Setar District. 108 teachers from the three schools were asked to response to items in the instruments OHI-Secondary about school climate. The instrument cosists of 44 items Likert scale The hypotheses were tested using ANOVA and Simple Regression analysis as well as Pearson correlation. Finding of the research shows that there is a significant difference in climate between schools in aspects such as academic emphasis, Affiliation, Resource Support and Principal Influence. There is , also a significant difference between school climate and students’ achievement in Mathematics and Science. Based on this research, sugesstions were made to improve students academic achievement.